Educational and learning resources for gifted and talented people: perspective of professional women from Argentina - Irueste, Paula; Saco, Ailen; Sarpakunnas, Pinja (2024)
Fil: Irueste, Paula. Universidad Nacional de Córdoba. Facultad de Psicología. Cátedra Psicología Clínica; Argentina.